Penyuluhan Penerapan Protokol Kesehatan Pada Masa Pandemi COVID-19 Di Kelurahan Manggala - Herlinda Mahdania Harun; Rusli Rusli; Salsabila Dwi Yunita (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
COVID-19 is a group of infectious disease caused by the corona virus (SARS-CoV-2). The spread of this virus so quickly to various countries in the world, including Indonesia, has resulted in COVID-19 becoming a global pandemic as a result of which efforts to prevent and control this disease are expected. Residents have an important role in breaking the chain of transmission of COVID-19 so as not to cause new infections. Given the mode of transmission from individual to individual, transmission can occur both at home, traveling, at work, places of worship, tourist areas as well as other areas where people interact socially. Therefore, this service aims to provide knowledge to the community in the form of counseling so as to apply health protocols during the COVID-19 pandemic. Counseling uses lecture, discussion, and question and answer methods. The results of the counseling activity that was held for a day showed that there was still a lack of awareness of the residents of the Manggala village regarding efforts to implement health protocols during the COVID-19 pandemic. The counseling was attended by stakeholders and received a good response, this can be seen from the questions from the local community.